Intercomparison of 51 radiometers for determining global horizontal irradiance and direct normal irradiance measurements. (August 2016) - Habte, Aron; Sengupta, Manajit; Andreas, Afshin; Wilcox, Stephen; Stoffel, Thomas
Highlights: We evaluated the performance of 51 radiometers for determining GHI and DNI data. Evaluation benefits system efficiencies of solar energy conversions installations. Under clear sky ±5% differences were observed among all GHI and DNI data. For GHI up to ±17% differences observed for high zenith angle under various skies. For some DNI data up to ±40% DNI difference was seen for cloudy sky and high zenith. Abstract: Accurate solar radiation measurements require properly installed and maintained radiometers with calibrations traceable to the World Radiometric Reference (WRR). This study analyzes the performance of 51 commercially available and prototype radiometers used for measuring global horizontal irradiances (GHI) or direct normal irradiances (DNI). These include pyranometers, pyrheliometers, rotating shadowband radiometers (RSR), 1 and a pyranometer with an internal shading mask deployed at the National Renewable Energy Laboratory's (NREL) Solar Radiation Research Laboratory (SRRL). The radiometers in this study were deployed for one year (from April 1, 2011, through March 31, 2012) and their measurements were compared under clear sky, partly cloudy, and mostly cloudy conditions to reference values of low estimated measurement uncertainties. Mean Bias Difference (MBD) and Root Mean Square Difference (RMSD) statistics were used as metrics to compare the GHI and DNI values from individual instruments with concurrent measurements using the reference instruments over time intervals of one-minute, 10-min, and hourly averages. Deviations from the reference irradiance measurements were calculated as a percent and W/m 2 of the reference value for solar zenith angles ranging from 17.5° to 85° (the range of available solar zenith angles throughout the year at SRRL, excluding data near sunrise and sunset). Under clear-sky conditions when the solar zenith angle was less than 60°, differences of less than ±5% were observed among all GHI and DNI measurements when compared to the reference radiometers. For GHI these normalized differences increased up to ±17% under mostly-cloudy and clear-sky conditions when the solar zenith angle was greater than 60°. The normalized differences were greater yet under mostly-cloudy conditions (approaching ±40%) for few DNI data sets at higher solar zenith angles. The intent of this paper is to present a general overview of each radiometer's performance based on the instrumentation and environmental conditions available at NREL.